QUANTIFICATION OF QUININE IN MEDICINAL PLANTS FROM EDE, NIGERIA USING HPLC - Abibu, Moshood Alamu; Adeniyi, B. O.; Muraina, T. A.; Adenipekun, O. D.; Isola, O. E.; Akinyoola, M. D. (FUDMA Journal of Sciences, 2025)
Nigeria, a West African country, is rich in medicinal plants traditionally used to manage various ailments. Quinine, a well-established antimalarial drug, has been widely used as a chemotherapeutic agent for treating malaria. This study aimed to develop and validate a rapid, simple, accurate and precise high-performance liquid chromatography (HPLC) method for the quantitatively determine the quinine content in three selected medicinal plants – Azadirachtai ndica (neem), Citrus aurantii folia (lime), and Mangifera indica (mango). Cold extraction method with vortex agitator was employed to obtain plant extracts. The separation and quantification of quinine were performed using an Agilent 1260 Infinity HPLC system equipped with a diode-array detector (DAD). Separation of quinine from extract was achieved on a Phenomenex Gemini C18 column in less than 2 minutes using an isocratic mobile phase of 30% acetonitrile and 70% double-distilled water and a flow rate of 1.0 mL/min at 254 nm. The standard calibration curve obtained was found to be linear R² = 0.9975. The analytical figures of merits were also evaluated for the percentage extraction recovery of quinine was 99.5%, the intraday precision as percent relative standard deviation was 1.14, it proved excellent % RSD which is less than 2 and of limits of detection (LOD) and limits of quantification (LOQ) were found to be 0.14µg/mL and 0.42µg/mL respectively. This study showed that, with the use of HPLC, quinine levels in these plants were accurately measured, thus, the method used was highly reliable, with excellent accuracy and precision. This study helps confirm whether...